Análise da estabilidade de um talude localizado em Fortaleza -ce - Siqueira, Caio Rogerio Sousa. (2023)
In the context of civil construction, safety is an extremely important consideration, given the complexity and multiple variables involved. This importance is even more accentuated in geotechnics, which requires special attention in projects, as in the case of slope stability analysis. This problem acquires significant relevance due to urban growth and, consequently, the occupation of hitherto unknown areas. However, it is notable that the analysis of slope stability is not common in the context of road operations. This happens due to disorderly growth, and any failure in slopes requires expensive recovery and often leads to significant consequences, both in environmental terms and in loss of human life. It is crucial to highlight that in many scenarios, these failures could be avoided or reduced if there was already existing knowledge. In this sense, the purpose of this study is to characterize the deformed soil sample present on the slope of Morro Santa Terezinha, located in the Mucuripe neighborhood, in Fortaleza - CE, which went through an intense process of urbanization and disorderly occupation from the 1980s onwards, and in 2015, in a landslide on part of the slope after a season of intense rain, followed by its revitalization, requalification and reurbanization process promoted by the Government of Ceará, together with the City of Fortaleza, and concluded in 2018. After to carry out this characterization, the slope stability was analyzed using the SLOPE/W software. The objective of this analysis was to determine the safety factor, which was obtained by carrying out five simulations, each using the methods of Fellenius, Bishop, Janbu, Spencer and Morgenstern-Price. These simulations aimed to verify the results found from different approaches. The results revealed that the type of soil is poorly graded sand, also, in all analysis methods used, the safety factor (FS) was below the critical value of 1.5, indicating slope instability and the chance of an imminent rupture. This situation reinforces the urgent need for attention and corrective measures to ensure the safety and integrity of road works, as well as to mitigate potential environmental impacts and risks to human life.